"It's good, they're like me; the same but different." An interpretative phenomenological analysis of the identities of women with down's syndrome. Issue 3 (29th November 2017) - Groves, Emma; Rayner, Kelly; Muncer, Steven
Abstract : Background: For people with disabilities, identity formation is based on responses to hierarchical values determined by able populations. Some adopt a disability identity, whereas others may seek to conceal their disability. No research has focused on how women with Down's Syndrome form an identity. Design: Eight women with Down's Syndrome took part in semi‐structured interviews designed to find out more about their individual and shared identities. The transcripts were analysed using interpretive phenomenological analysis. Findings: Negative assumptions of others and oppressive, paternalistic care often lead to a lack of ownership over narratives. "Finding a place in society" is an attempt to challenge this and gain a sense of ownership over their lives. Conclusions: This research uncovered the individual and shared identities that women with Down's Syndrome construct. Services need to be aware of the role they have in supporting these women to develop autonomy and ownership over their lives.